Ciliate ecology in the eutrophic Bay of Quinte, Lake Ontario: Community structure and feeding characteristics†. Issue 1 (2nd January 2020) - Munawar, M.; Niblock, H.; Fitzpatrick, M.; Lorimer, J.
Abstract : The ciliate community of the Bay of Quinte, Lake Ontario was assessed over a six year period from 2003 – 2008. One eutrophic site in the upper bay (Belleville) and one more oligotrophic site in the lower bay (Conway), were included in the survey. Both sites contained a mixture of Haptoria, Strobilidium, Halteria, Strombidium, and Vorticella, although the relative proportions varied among sites resulting in different community structures. Ciliate biomass was found to be significantly higher at Belleville (mean: 100.2 ± 14.1 mg m −3 ) compared to Conway (mean: 37.1 ± 3.5 mg m −3 ), but could be explained by sudden pulses of Haptoria, primarily species of Mesodinium, which peaked as high as 678.1 mg m −3 . Canonical Correspondence Analysis showed a clustering of Halteria, Strobilidium, Tintinnina, Urotricha and Vorticella with surface temperature along with autotrophic picoplankton as a potential prey item. The results suggest that autotrophic picoplankton may be an important food resource for the ciliate community and that there is a strong seasonal gradient to community structure. Future research should be directed at understanding how ciliates influence the transfer of both primary and secondary production to higher trophic levels.